Video streaming and the communication to the public right in the United States and European Union - Makeen, Makeen Fouad (Research Handbook on Intellectual Property and Digital Technologies, 2020)
This chapter examines the application of copyright law to video streaming in the US and the EU. Since the Berne Convention and the WIPO Copyright Treaty established international norms that national laws need to follow, the relevant provisions of these two international instruments are used as the archetype; US and EU laws’ compatibility with them is examined here. This chapter demonstrates that through the communication to the public right, or its equivalent, copyright law adequately protects authors against the three existing types of video streaming: webcasting, on-demand streaming and internet retransmission of broadcasts. It argues that in the context of video streaming, the exclusive nature of the communication to the public right must be preserved. Therefore, this chapter maintains that any national law that recognises a compulsory licence mechanism to cover this new technology, or adopts the service zone theory to exempt certain types of video streaming from copyright liability, may run the risk of being in breach of its international obligations.
Section: Research Handbook on Intellectual Property and Digital Technologies